Beyond Tumors: The Pivotal Role of TRIM Proteins in Chronic Non-Tumor Lung Diseases - Huang X; Yu W; Wei A; Wang X; Chen S (Journal of Inflammation Research)
Xiangfei Huang, Wen Yu, Aiping Wei, Xifeng Wang, Shibiao Chen Department of Anesthesiology, The First Affiliated Hospital of Nanchang University, Nanchang, 330006, People’s Republic of ChinaCorrespondence: Shibiao Chen, Department of Anesthesiology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China, Email Chenlaoshi1111@163.comAbstract: While TRIM proteins are extensively studied in the context of lung tumors, their roles in non-tumor chronic lung diseases remain underexplored. This review delves into the emerging significance of TRIM family proteins in the pathogenesis of idiopathic pulmonary fibrosis (IPF), asthma, chronic obstructive pulmonary disease (COPD), and pulmonary hypertension (PH). TRIM proteins modulate key pathological processes, including inflammation, fibrosis, and cellular remodeling, contributing to disease progression. We highlight their potential as biomarkers and therapeutic targets, offering promising avenues for drug development in these debilitating respiratory disorders. However, the translation of these findings into clinical applications faces significant challenges. These include the dual functional nature of TRIM proteins, their context-dependent roles, the complexity of their downstream signaling networks, and the limitations of current therapeutic strategies in achieving tissue-specific targeting with minimal off-target effects. Addressing these challenges will require innovative approaches and interdisciplinary efforts to unlock the therapeutic potential of TRIM proteins in non-tumor chronic lung diseases.Keywords: TRIM proteins, chronic lung diseases, idiopathic pulmonary fibrosis, COPD, asthma, pulmonary hypertension